Brand Communications Effect, Brand Images, and Brand Trust Over Loyalty Brand Building at PT Sanko Material Indonesia - Reni Afriani; Rhian indradewa; Tantri Yanuar R Syah (Penerbit Kemala Indonesia, 2019)
This study aimed to analyze the effect of brand communication on brand image, brand communication, and brand trust over loyalty brand building at PT. Sanko Material Indonesia. In this study, we use quesionaries to assess loyality brand building to all distributors and other business companies near 250 companies. Here, we take 160 respondents who were considered to have adequately represented a population studied brand loyality. The sampling technique in this study, we use Convenience Sampling method which is a sampling method based on the convenience factor where the respondents discuss and meet at survey location. We use analytical model e.g. Structural Equation Modelling with the AMOS 21 Program to obtain the result. The results shows, a Brand communication had a positive and significant effect on brand image. The implication of loyality brand building is a better than brand communication carried out by PT. Sanko Material Indonesia. Brand communication have a positive and significant effect on brand trust. It means that the better brand communication is increased consumer confidence. Brand image also has positive and significant effect on brand trust as well as a positive and significant influence of brand trust on brand loyalty. This means that the better brand image with higher brand trust and the higher consumer confidence in products of PT. Sanko Material Indonesia.